2016
DOI: 10.1016/j.jmaa.2015.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Estimates for the blowup time of a combustion model with nonlocal heat sources

Abstract: Please cite this article in press as: N. Wang et al., Estimates for the blowup time of a combustion model with nonlocal heat sources, J. Math. Anal. Appl. (2016), http://dx. AbstractIn this paper, we establish the lower and upper bounds for the blowup time of the solution to a system of parabolic equations with nonlocal nonlinearities which appears in a model of combustion. Different techniques are applied to deal with the problems in different space dimensions. We also discuss non-simultaneous blowup phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It can be found that the blow-up time T is nonincreasing in the size of the initial data (e.g., [13,14]). Then we can choose suitable initial data such that 1 ˇT C˛T > 0 due toˇ>˛.…”
Section: Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that the blow-up time T is nonincreasing in the size of the initial data (e.g., [13,14]). Then we can choose suitable initial data such that 1 ˇT C˛T > 0 due toˇ>˛.…”
Section: Proofmentioning
confidence: 99%
“…The results about Fujita blow-up phenomena in unbounded domains can be found in [7,8] and the references cited there. For fully coupled systems, one can refer to [9][10][11][12][13][14][15][16][17][18][19][20][21] for singularity of solutions. For singular or degenerate problems, one can find the corresponding results in [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by Refs. [8][9][10][11][12][13][14][15][16], this paper studies the lower bound of blow up time for solutions of slow reaction-diffusion equations (1)-( 5) with different boundary conditions when m > 1n > 1, and generalizes the existing results. The results can better describe the reaction diffusion problems with the cross influence of two variables in physical, chemical and hydrodynamic problems.…”
Section: Introductionmentioning
confidence: 99%
“…Blow-up at a finite time and lower bound of blowing up time of solution for the parabolic equations are studied in [4,5]. The lower bound of blowing up time for solutions of other similar equations or equation set is shown in [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%